Factors affecting log-transformed muscle 137Cs concentrations in wild boars in Fukushima Prefecture over 14 years - Hisashi Komatsu; Shiori Ikushima (PLoS ONE, 2026)
The March 2011 Fukushima Daiichi Nuclear Power Plant accident resulted in extensive radiocesium contamination of forest ecosystems. Wild boars ( Sus scrofa ) are a key indicator species because of their high radiocesium accumulation; however, long-term spatiotemporal patterns and biological drivers of contamination have not been fully evaluated using a prefecture-wide dataset. We analyzed monitoring data from 3,609 wild boars collected across Fukushima Prefecture over 14 years (FY2011–FY2025). By integrating individual-level measurements with spatial soil deposition data, we fitted three mixed-effects models to ln-transformed muscle 137 Cs concentrations to quantify regional ecological half-lives, assess dietary influence using stomach-content 137 Cs where available, and evaluate associations with biological attributes such as sex and growth stage. Ecological half-lives of muscle 137 Cs ranged from 3.0 to 9.2 years across regions, shorter than the physical half-life of 30.1 years, with the most rapid decline observed in Hamadori. Although long-term decreases were evident, a transient increase occurred in Nakadori in FY2022, indicating the influence of localized ecological variability. In individuals with paired stomach-content measurements, muscle 137 Cs increased with stomach-content 137 Cs, supporting a dietary pathway for short-term variation; however, paired stomach-content data were limited in some regions. Growth stage was significantly associated with muscle 137 Cs, with evidence consistent with higher adult burdens relative to younger animals. These results show that radiocesium dynamics in wild boars reflect regional recovery processes, dietary pathways, and biological attributes. Our findings emphasize the value of long-term, multi-variable monitoring frameworks for assessing radiological risk and ecosystem recovery in wildlife inhabiting post-accident landscapes.